x + 4 = 25
x = 25 - 4
x= 21
x - 2 = 6
x = 6 + 2
x = 8
9x = -27
x = -27 : 9
x= -3
y/-6 = 2
y = 2 * -6
y = -12
m + 3.7 = 2.4
m = -1.3
a + 13 = 10
a= 10 - 13
a = -3
d - 7 = -9
d = -9 +7
d = -2
-7x = -63
x = -63 : -7
x = 9
x/4 = -14
x = -14 * 4
x= -56
x - (-66.09) = 102.8
x = 36.71
n + (-8) = -14
n - 8 = -14
n = -14 + 8
n = -6
k - (-83) =121
k + 83 = 121
k = 121 - 83
k =38
-5e = -400
e = -400 : -5
e = 80
x/6 = -6
x = -6 * 6
x = -36
-5.6 = 0.8x
x = -5.6 : 0.8
x= -7
x + 36 = -100
x = -100 -36
x = -136
x - 327 = -665
x = -665 + 327
x = -338
-11x = 275
x = 275 : -11
x = -25
-28 = a/-13
a= -28 * -13
a = 364
c/-0.29 = 5.5
c = 5.5 * (-0.29)
c =-1.595
-27 = c + 27
c = -27 - 27
c = - 54
a - (-163) = -392
a +163 = -392
a = -392 -163
a = -555
-21y = -756
y = - 756 : -21
y = -36
-80 = x/15
x = -80 * 15
x= -1200
0.12 = y/0.12
y = 0.12 * 0.12
y = 0.0144